Purification of glucomannan from salep: Part 1. Detailed rheological characteristics - Kurt, Abdullah; Kahyaoglu, Talip (ELSEVIER SCI LTD, 2017)
The aim of this study was to investigate the effects of different extraction temperatures (25, 55 and 85 degrees C) on the rheological characteristics of glucomannan (GM) purified from salep. GM was isolated using the following method: extraction of GM with water, removal of impurities by centrifugation and precipitation of GM with ethanol. The extraction yield of GM was approximately 45% for all products. Higher GM (95%) and lower starch (3%) contents were obtained for GM25. GM25 showed higher apparent and intrinsic viscosity, storage and loss modulus and lower activation energy than GM55 and GM85. The addition of different salts and sugars did not affect viscosity due to the non-polyelectrolyte behavior of GM. Gel behavior of purified samples appeared at pH 9. The usage of salep in milk was reduced by purification. These results are potentially useful for widening the applications for salep and for furthering research and development of GM. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Salep; Glucomannan; Purification; Rheology; LOCUST BEAN GUM; KONJAC GLUCOMANNAN; PHYSICOCHEMICAL CHARACTERIZATION; FUNCTIONAL-PROPERTIES; CHEMICAL-COMPOSITION; INTRINSIC-VISCOSITY; DILUTE-SOLUTION; SEED GUM; EXTRACTION; POLYSACCHARIDES; Chemistry; Polymer Science